Zebra Finch Song Phonology and Syntactical Structure across Populations and Continents—A Computational Comparison - Lachlan, Robert F.; van Heijningen, Caroline A. A.; ter Haar, Sita M.; ten Cate, Carel (Frontiers in Psychology, 2016)
Learned bird songs are often characterized by a high degree of variation between individuals and sometimes between populations, while at the same time maintaining species specificity. The evolution of such songs depends on the balance between plasticity and constraints. Captive populations provide an opportunity to examine signal variation and differentiation in detail, so we analyzed adult male zebra finch (Taeniopygia guttata) songs recorded from 13 populations across the world, including one sample of songs from wild-caught males in their native Australia. Cluster analysis suggested some, albeit limited, evidence that zebra finch song units belonged to universal, species-wide categories, linked to restrictions in vocal production and non-song parts of the vocal repertoire. Across populations, songs also showed some syntactical structure, although any song unit could be placed anywhere within the song. On the other hand, there was a statistically significant differentiation between populations, but the effect size was very small, and its communicative significance dubious. Our results suggest that variation in zebra finch songs within a population is largely determined by species-wide constraints rather than population-specific features. Although captive zebra finch populations have been sufficiently isolated to allow them to genetically diverge, there does not appear to have been any divergence in the genetically determined constraints that underlie song learning. Perhaps more surprising is the lack of locally diverged cultural traditions. Zebra finches serve as an example of a system where frequent learning errors may rapidly create within-population diversity, within broad phonological and syntactical constraints, and prevent the formation of long-term cultural traditions that allow populations to diverge.